Hubungan Pengetahuan Ibu, Peran Keluarga dan Perawatan Tali Pusat dengan Lama Lepas Tali Pusat Pada Bayi Baru Lahir yang Pernah Bersalin di RSIA Marissa Palembang Tahun 2023 - Karisma, Novia; ismed, syarifah; Afrika, Eka (NHM PRESS, 2023)
Umbilical cord care is the act of caring for or maintaining the umbilical cord of a newborn baby after it is cut until it falls off. Proper and correct umbilical cord care will have a positive impact, where the umbilical cord will fall off on the 5th and 7th days without complications. On the other hand, negative impacts of improper umbilical cord care include the risk of neonatal tetanus. The purpose of umbilical cord care is to prevent the occurrence of tetanus in newborns caused by the entry of tetanus bacteria spores into the body through the umbilical cord, whethere from tools, use the medications, powders, or leaves sprinkled onto umbilical cord, which can lead to infections. The purpose of this study was to determine the relationship of mother’s knowledge, family role, umbilical cord care to umbilical cord separation time in newborns at Marissa Mother and Child Hospital Palembang in 2023. This study was an analytical survey where the researcher explored how and why the phenomenon of maternal health occured. This analytical survey used a cross-sectional approach to study the dynamic correlation between risk factors and effects, through observation or data collection at single point in time. The statistical test result showed that the ρ value of 0.007 ≤ α 0.05 for mother’s knowledge, the ρ-value for family role 0.028 ≤ α 0.05, and the ρ-value for umbilical cord care 0.045 ≤ α 0.05. Therefore, it could be concluded that was a significant relationship of mother’s knowledge, family role, family role, umbilical cord care to umbilical cord separation time in newborns at Marissa Mother and Child Hospital Palembang in 2023.